Key Ideas
Solving the Question
We're given:
Determine f(-5):
![f(a) = 3a - a^2\\f(-5) = 3(-5) - (-5)^2\\f(-5) = -15 - 25\\f(-5) = -40](https://img.qammunity.org/2023/formulas/mathematics/college/kju65v2r1u3x0e9vprkdercq9ekob2m9od.png)
Therefore, this statement is true.
Determine f(4):
![f(a) = 3a - a^2\\f(4) = 3(4) - (4)^2\\f(4) = 12 - 16\\f(4) = -4](https://img.qammunity.org/2023/formulas/mathematics/college/oz7tx49k2iqb63k1ry0hcjz1yxjetoiyqf.png)
Therefore, this statement is true as well.
Determine f(-1):
![f(a) = 3a - a^2\\f(-1) = 3(-1) - (-1)^2\\f(-1) = -3 - 1\\f(-1) = -4](https://img.qammunity.org/2023/formulas/mathematics/college/gfq0omnbgpzz55n6uidbzcwiyu2zcze2xv.png)
Therefore, this statement is not true.
Determine f(0):
![f(a) = 3a - a^2\\f(0) = 3(0) - (0)^2\\f(0) = 0 - 0\\f(0)=0](https://img.qammunity.org/2023/formulas/mathematics/college/d256l3km2bzjdiuogm52js5vghn88wi6ic.png)
Therefore, this statement is also not true.
Answer
f(-5) = -40
f(4) = -4